Model the effectiveness of a systematic process of technical re-equipment of production - Безугла, Дар’я Валеріївна (Technology audit and production reserves, 2015)
In the article the modern definition of "technical re-equipment of production", outlines the methodological approach to the analysis of its nature and content, as a system process efficiency is determined by performing technical-technological, organizational-economic and innovation-implementing subsystems consisting of technical object retooling. Developed the optimization mathematical of model system function efficiency of technical industry re-equipment aimed to the combination consisting of generalized analytical performance ratio of all nominated subsystems defined functional and technical components. Essential author's suggestion is calculating a priori and actual performance across all functional components of technical upgrading facility, comparison of achieved performance and efficiency and using of partial indices composed of system function performance. The possibility of interpreting the indicators of efficiency of the system function is not only to assess the outcomes of technical re-equipment of production, but also to identify the functional components of the overall system, which targets technical upgrading achieved with deviations from planned values. Proposed author deals with both scientific-methodological significance and practical orientation that tested by the example of a concrete manufacturing plant and can be implemented in other enterprises industries.